Evaluation of retinal vascular density and related factors using OCTA in children and adolescents with myopia without maculopathy. Issue 1 (January 2023) - Lin, Lingli; Zhang, Xiaohan; Huang, Cuiting; Zhang, Zhaode
Background: Myopia is the most common ophthalmic condition worldwide with a rapidly increasing prevalence. This study aimed to compare the retinal microvasculature in the superficial capillary plexus (SCP) in children and adolescents with mild and moderate/high myopia using optical coherence tomography angiography, determine the relationship between retinal parameters and axial length (AL), and understand the occurrence and progression of myopia in microcirculation. Methods: This prospective observational study included 39 participants with mild myopia and 33 participants with moderate/high myopia. Vessel density (VD) and perfusion density (PD) in the SCP, the foveal avascular zone (FAZ), and AL were compared between the groups and the relationship between these retinal parameters and AL was assessed. Results: No difference in SCP VD or PD was observed between the two groups. The FAZ did not differ significantly between groups whereas significant differences in age, height, refractive status, and AL were observed. Significantly shorter AL was observed in participants with mild myopia compared with the moderate/high myopia group. Age was positively correlated with height (r = 0.852) and refractive status was negatively correlated with AL (r = −0.588). AL was positively correlated with VD (r = 0.317) and PD (r = 0.308) in the SCP and AL was negatively correlated with the FAZ (r = −0.434). Conclusions: This study revealed that superficial foveal microvessel density was unaffected in children and adolescents without pathological myopia. However, myopia progression was associated with a change in AL, and an AL increase altered macular blood flow.